PENGEMBANGAN DESAIN PERMAINAN BERBASIS ADVENTURE EDUCATION DALAM KEMAMPUAN KOMUNIKASI DI KELAS 5 SEKOLAH DASAR - Sri Aprilia, Arifina; Ardiyanto, Asep; Fita Asri Untari, Mei (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Adventure is an interesting and challenging activity, such as engaging in explorative activities that uncover new things never previously discovered. Education is a learning process aimed at developing students' potential and improving the learning process. Communication skills refer to a process of interaction or reciprocal relationships between individuals who send and receive messages from one another. Based on this research, after students received an adventure-education-based game design, they became more interested in enhancing their communication skills. SDN 2 Cepokomulyo achieved a 90% interest rate, SDN 2 Triharjo reached 94%, and SDN 1 Sojomerto reached 95%. From this, it can be concluded that these elementary students are highly interested in learning activities developed using adventure-education-based games, making this approach highly effective.